CONFIXED VERBS WITH NEGATIVE SEMANTICS OF ACTION CONSEQUENCES IN MODERN RUSSIAN - Zara Godizova; Tsyan’ Wang (Гуманитарные и юридические исследования)
The confix ways of verbal action, which expresses negative semantics of action consequences, are under discussion in the article. It seems relevant for the study to find out whether the general idea of the negative consequences of action is related to the conixed word-building model, to analyze the interaction of grammatical and lexical semantics of those type of verbs, to determine the features of aspectual situations, to reveal stylistic features of their functioning, to reveal the complexes of meanings expressed by conixed word-building types bearing the negative consequences semantics. It is established that the negative semantics of action consequences can be presented explicitly or implicitly to a greater or lesser extent; the representation of the negative consequences of action can be expressed by the verb form or it can. require a certain context. The semantic markers, that signal excessive intensity or duration of action, are identified. All verbal actions, which denote the negative result, are presented as a functional and semantic field; the central and peripheral components of the field are determined depending on the degree of explicitness of the negative consequences of action, as well as its intensity, excessiveness and duration.. Regularity and efficiency of a verb type is also taken into account. It is defined due to what factors the semantics of negative consequences of an action is created; it is specified in each specific action. The conix ways of verbal action with the semantics of the negative consequences of the action are investigated from the point of view of functionality and stylistics, regularity and productivity of derivational type, species correlation. The reasons for the predominant uniformity of these ways of action are identified. It is established that the verbs under analysis can cover multiple situations and convey the complex of meanings, since the semantics of the negative consequences of action is a consequence of excessive manifestation of an action, its intensity, duration and sometimes multiplicity. The derived verbs are a compact means of expressing complex semantics, which correlates with the descriptive construction. It is concluded that the presence in the Russian language of such a variety of ways of action with the meaning of the negative consequences of action, which were the result of excessively intense or prolonged action of the original verb, indicates the importance of a certain concept (or several concepts) for Russian speakers and for the Russian language picture of the world.